Ideologies, structures, and contingencies: writing the history of British criminal justice since 1975 - Chris A. Williams (Revue Française de Civilisation Britannique)
The history of British criminal justice has been characterised by a massive increase in output since 1975. This article explores four key interventions and examines their impact. Foucault's view of the birth of the prison, though not confirmed by research, has led to better knowledge of cultures of control. Similarly, the Warwick School's treatment of the eighteenth-century criminal law has sparked an interest in a wide variety of court records. Storch's work on the new police has led to the rehabilitation of the old police. Work on criminal statistics has not reliably defined trends in crime, but has served to map the effort of the criminal justice system. Overall, despite a trend towards more complex explanations, the initial promise of criminal justice history – as a vehicle for 'total history' – is being fulfilled.